Analisis Pelaksanaan Peran Dewan Keamanan PBB Dalam Mengawasi Penggunaan Senjata Nuklir - Setiawan, Irman; Harisman, Harisman (UNES Law Review, 2024)
One of the primary focuses of International Law and its member countries is the resolution of disputes caused by armed conflicts. Armed conflicts, which have existed since ancient times, are generally triggered by various factors, but often, conflicts between countries arise due to the desire to control territories within a country. This study focuses on the normative legal research method, also known as the positive law research method, doctrinal law research method, and pure law research method. This method examines documented laws or customary social practices. In normative research, most of the data is obtained from secondary data sources, including primary, secondary, and tertiary legal materials. Additionally, the United Nations Security Council has the authority to order the International Atomic Energy Agency to inspect and verify a country's nuclear activities and facilities to ensure compliance with the NPT and IAEA protection agreements. If countries do not comply with or withdraw from the NPT, the Security Council can take action under Chapter VII of the UN Charter, including imposing sanctions or other enforcement actions, if deemed necessary. The UN Security Council is responsible for establishing a global arms regulation system. The system aims to reduce military power in various countries and enhance global peace and security. The Security Council must design a plan that will then be communicated to United Nations (UN) members regarding arms control regulations. Moreover, it is an important duty of the United Nations Security Council to ensure that all member countries comply with international treaties on Nuclear Weapons